Papel das proteínas Yops de Yersinia pseudotuberculosis na ativação dos linfócitos B - Medeiros, Beatriz Maria Machado [UNESP]; Souza, Cleide Dos Santos; Higuti, L. [UNESP]; Maia, Jose Mario Lourenco [UNESP]; Silva, Eloisa Elena Cangiani [UNESP] (My University, 2003)
The virulence plasmid common to pathogenic Yersinia species encodes a number of secreted proteins denoted Yops (Yersinia outer proteins). The Yops effectors have been related to a set of biological properties, including resistance to phagocytosis, cytotoxicity and dephosphorilation of host proteins. However, the interaction of Yops with the adaptive immune response is not clear. Yops secreted by Yersinia enterocolitica O:3 provoke policlonal activation of B lymphocyte, when inoculated in mice. In this work, Yops secreted by K pseudotuberculosis were inoculated by intravenous route in SPF Swiss mice, with the purpose of verify the in vivo role of these proteins in the splenic B lymphocyte activation. The kinetics of production of specific and nonspecific immunoglobulins of the different isotypes (IgG, IgA and IgM), was investigated by the technique of ELISPOT The presence of specific anu-Yersinia antibodies in the serum of the inoculated animals was also investigated by ELISA. It was observed a significant increase only in the number of nonspecific IgG-secreting lymphocytes, on the 21 st day after inoculation (a 2.5-fold increase compared to control). The number of lymphocytes secreting other isotypes of Ig was similar to the controls, with exception of IgA, which was 3.1-fold impaired on the 7th day after inoculation. Turning to specific Ig-secreting cells, the response of the animal was very individual. In some inoculated mice, it was detected anu-Yersinia IgG-secreting cells on the 7 th and 14 th days after inoculation and IgM-secreting cells on the 7 th and 28 th days after inoculation. On the other hand, IgG anù-Yersinia antibodies were detected in the sera of all inoculated mice on all days after inoculation, with a peak on the 28 th day; IgM anti- Yersinia were detected only on the 7th day after inoculation. These results demonstrate that it exist a difference in the immunomodulatory capability of Yops secreted by Y. pseudotuberculosis and Y. enterocolitica.
Role of Yops of Yersinia pseudotuberculosis in B lymphocyte activation
Keywords: Experimental infection; Policlonal activation; Specific antibodies; Yersinia pseudotuberculosis; Yops; antibody; bacterial protein; immunoglobulin A; immunoglobulin G; immunoglobulin M; unclassified drug; yops protein; animal cell; animal experiment; animal model; antibody production; antibody specificity; B lymphocyte; B lymphocyte activation; bacterial virulence; controlled study; cytotoxicity; dephosphorylation; enzyme linked immunosorbent assay; enzyme linked immunospot assay; immune response; immunoglobulin producing cell; immunoglobulin production; immunomodulation; in vivo study; mouse; mouse strain; nonhuman; phagocytosis; plasmid; polyclonal activation; protein interaction; protein secretion; spleen cell; Yersinia; Yersinia enterocolitica